First and second language acquisition: Towards a reconcillation - Nau, Nicole (Lingua Posnaniensis, 2014)
For the past two decades, research on first language acquisition on the one side, and on second language acquisition and learning on the other have largely developed separately, probably as a reaction to the failure of earlier attempts to use the same methods or simply transfer insights gained in one of the fields to the other. T his article argues that a reconciliation may be fruitful, provided that different aspects which have often got blurred in the discussion are considered separately. These aspects include the assessment of multilingualism and monolingualism, the age factor and the definition of “first” and “second” language, the understanding of linguistic competence and of completeness of acquisition, different forms of acquisition and learning, and uniformity vs. individual differences in the process of language acquisition. By challenging some widely held views on characteristics of first language acquisition and its differences to second language learning, more fine-grained research questions are revealed, some of which have been addressed in recent studies on language acquisition and multilingualism